Animation of Free Time and Support for Psychomotor Development of Infants Aged Over 3 Months - Małgorzata Paczyńska-Jędrycka (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2020)
This article constitutes a desk study regarding animation of free time and its influence on the psychomotor development of infants aged over 3 months. The article discusses the concept of free time of infants. The motor and psychological development of children between the age of three months to one year is presented. Moreover, different ways of spending free time by the parent and child are shown. The aim of this article is to raise awareness of the role of supporting early child development through appropriate selection of games and other activities in line with the individual stage of development of an infant. The article has been prepared based on a literature review (including PubMed, Research Gate, EBSCO) as well as analysis of selected offers of commercial animation activities available in the city of Poznań, taking into account the individual stages of development and their impact on the comprehensive development of infants. Moreover, a list of activities recommended for children which are adequate to specific periods of their development was also prepared.